Pengaruh Motivasi Kerja, Sistem Informasi Manajemen Penggajian dan Kemampuan Komunikasi Interpersonal terhadap Kinerja Karyawan ( Studi Kasus pada PT Bank Mandiri tbk KCP Sungguminasa ) - Muh Arif, Aminuddin; Abdillah Mubarak (Jurnal Mirai Management, 2022)
This study aims to test and at the same time examine Work Motivation, Payroll Management Information Systems, and Interpersonal Communication Skills on Employee Performance. This study was conducted at the PT Bank Mandiri office which is domiciled and active in Gowa Regency. This study involved 32 people as the population and the sample used was a saturated sample so that the total sample was the total population. This study uses primary data collected using a questionnaire. Furthermore, the data were analyzed using the SPSS statistical tool using the multiple regression analysis method. The data were tested through several stages of testing such as validity, reliability, normality and heteroscedasticity tests. Furthermore, to prove the hypothesis proposed in this study, it will be seen through the coefficient of determination test, partial test (t-test) and simultaneous test (f-test). The results of this study partially prove that the variables of Work Motivation, Payroll Management Information System, and Interpersonal Communication Ability have a positive and significant impact on employee performance at PT Bank Mandiri KCP Sungguminasa. Meanwhile, simultaneously, the variables of Work Motivation, Payroll Management Information System, and Interpersonal Communication Ability have a positive and significant effect. Of the three independent variables, the dominant Interpersonal Communication Ability variable has an effect on improving employee performance at PT Bank Mandiri KCP Sungguminasa. Keywords: Work Motivation, Payroll Management Information System, Interpersonal Communication and Employee Performance.